ANALISIS PERFORMANSI JARINGAN VERY SMALL APERTURE TERMINAL INTERNET PROTOCOL (VSAT IP) PADA PT BANK KALBAR PONTIANAK - ., Nurjali (Faculty of Engineering, Universitas Tanjungpura, 2016)
Abstract PT Bank Kalbar Pontianak is one of the enterprises engaged in banking services. To win the competition and become the leading bank in West Borneo, Bank Kalbar have a vision and mission. The Bank's vision is to become a leading bank Kalbar (regional champion) in the respective regions with competitive products and services, has an extensive network, and professionally managed in boosting regional economic growth. vision, as mentioned above in addition be based on a foundation of good corporate governance (GCG) and risk management, should also be supported by three pillars, namely a strong institutional resistance, ability as an agent of regional development and the ability to serve the needs of the community. Problem in PT Bank Kalbar Pontianak associated with computer networks is the quality of the data that is less than the maximum network which broke the network, the data transfer speed is less than the maximum time for each Uploud and Download long enough. QoS (Quality of Service) is technology that applied to the WAN (Wide Area Network) that allows network administrators to be able to handle a variety of effects due to congestion (congestion) on the traffic flow of packets in the network. QoS parameters are delay / latency, jitter, packet loss, throughput, MOS, echo cancellation and PDD. QoS is needed to minimize packet loss, delay, latency and delay variation (jitter), convincing performances, mixing voice and data packets on the network is dense, and can optimize the queues to priority services such as traffic voice and traffic shaping / buffering on the network WAN. Based on calculations, it can be concluded the average value for each parameter for peak hours and hours of quiet is a delay of 24.36 ms with the index of 4, jitter of 20.44 ms with the index of 4, throughput amounted to 28.48% with the index of 4 , packet loss amounted to 0% with the index of 4. Kata kunci - Quality of Service, Delay, Jitter, Throughtput, Packet Loss.